EVALUATING TAX INFORMATION SYSTEMS: IMPLICATIONS FOR MSME TAXPAYER COMPLIANCE AND THE ROLE OF TAX SOCIALIZATION - Sofianty, Diamonalisa; Mat Udin, Noraza (JRAK, 2025)
Tax compliance remains a persistent challenge for Micro, Small, and Medium Enterprises (MSMEs), primarily due to limited knowledge and inadequate access to tax information. This study investigates the effect of tax socialisation on taxpayer compliance, with tax information systems serving as a mediating variable. A quantitative approach was employed, with data collected from 90 MSME owners through purposive sampling. Path analysis using SmartPLS revealed that tax socialisation has a positive and significant effect on tax compliance. Furthermore, tax information systems were found to partially mediate this relationship by enhancing access to and understanding of tax-related content. These findings underscore the importance of combining socialisation initiatives with user-friendly digital systems to boost compliance. Governments are encouraged to strengthen outreach programs and develop accessible information platforms tailored to the specific needs of MSMEs. Such initiatives are expected to improve voluntary compliance and reduce administrative burdens in the long term.